2010
DOI: 10.1111/j.1365-2672.2010.04885.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-inducing effect of diketopiperazine disulfides produced by Aspergillus sp. KMD 901 isolated from marine sediment on HCT116 colon cancer cell lines

Abstract: Aims:  Research is to identify the bioactive secondary metabolites produced by Aspergillus sp. KMD 901 isolated from marine sediment and to assess their apoptosis‐inducing effects. Methods and Results:  Aspergillus sp. KMD 901 was isolated from marine sediment obtained from the East Sea of Korea. An ethyl acetate extract of KMD 901 exhibited potent cytotoxic activity towards five cancer cell lines (HCT116, AGS, A549, MCF‐7 and HepG2). Sequencing of the internal transcribed spacer (ITS) region in this strain al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…These metabolites possess a broad spectrum of biological activities, including antibacterial, antiviral and antifungal activities (Witiak and Wei, 1990;Gardiner et al, 2005;Borthwick, 2012). Several naturally occurring ETPs, such as gliotoxin (antitumor activity) (Cole and Cox, 1981), chaetocin (antimyeloma activity) (Isham et al, 2007), and acetylaranotin (pro-apoptotic activity) (Neuss et al, 1968;Choi et al, 2011) have attracted considerable attention in recent years due to their pronounced cytotoxic activities against various human cancer cell lines (Dubey et al, 2013;Boyer et al, 2013;Reece et al, 2014). The essential structural element of ETPs responsible for the observed biological properties is attributed to the sulfur moiety in the oxidized disulfide form and/or the reduced dithiol form (Chai and Waring, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites possess a broad spectrum of biological activities, including antibacterial, antiviral and antifungal activities (Witiak and Wei, 1990;Gardiner et al, 2005;Borthwick, 2012). Several naturally occurring ETPs, such as gliotoxin (antitumor activity) (Cole and Cox, 1981), chaetocin (antimyeloma activity) (Isham et al, 2007), and acetylaranotin (pro-apoptotic activity) (Neuss et al, 1968;Choi et al, 2011) have attracted considerable attention in recent years due to their pronounced cytotoxic activities against various human cancer cell lines (Dubey et al, 2013;Boyer et al, 2013;Reece et al, 2014). The essential structural element of ETPs responsible for the observed biological properties is attributed to the sulfur moiety in the oxidized disulfide form and/or the reduced dithiol form (Chai and Waring, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…57 The compound was later identified in Aspergillus terreus , the producer of lovastatin. 8 Subsequent bioactivity studies have shown that acetylaranotin ( 1 ) and its derivatives display an array of interesting biological activities including the inhibition of viral RNA polymerase, 6 the induction of apoptosis in cancer cell lines 9 and antifungal activity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…KMD 901 and determined that it induces apoptosis in HCT116 colon cancer cells. 13 Here, we report the first total synthesis of 3 , which was enabled by an eight-step, enantioselective synthesis of a key amino acid building block, 7 .…”
mentioning
confidence: 99%